Mineralogy of Vera Rubin Ridge From the Mars Science Laboratory CheMin Instrument. Issue 9 (24th September 2020) - Rampe, E. B.; Bristow, T. F.; Morris, R. V.; Morrison, S. M.; Achilles, C. N.; Ming, D. W.; Vaniman, D. T.; Blake, D. F.; Tu, V. M.; Chipera, S. J.; Yen, A. S.; Peretyazhko, T. S.; et al.
Abstract: Vera Rubin ridge (VRR) is an erosion‐resistant feature on the northwestern slope of Mount Sharp in Gale crater, Mars, and orbital visible/shortwave infrared measurements indicate it contains red hematite. The Mars Science Laboratory Curiosity rover performed an extensive campaign on VRR to study its mineralogy, geochemistry, and sedimentology to determine the depositional and diagenetic history of the ridge and constrain the processes by which the hematite could have formed. X‐ray diffraction (XRD) data from the CheMin instrument of four samples drilled on and below VRR demonstrate differences in iron, phyllosilicate, and sulfate mineralogy and hematite grain size. Hematite is common across the ridge, and its detection in a gray outcrop suggest localized regions with coarse‐grained hematite, which commonly forms from warm fluids. Broad XRD peaks for hematite in one sample below VRR and the abundance of FeOT in the amorphous component suggest the presence of nanocrystalline hematite and amorphous Fe oxides/oxyhydroxides. Well crystalline akaganeite and jarosite are present in two samples drilled from VRR, indicating at least limited alteration by acid‐saline fluids. Collapsed nontronite is present below VRR, but samples from VRR contain phyllosilicate with d(001) = 9.6 Å, possibly from ferripyrophyllite or an acid‐altered smectite. The most likely cementing agents creating the ridge are hematite and opaline silica. We hypothesize late diagenesis can explain much of the mineralogical variation on the ridge, where multiple fluid episodes with variable pH, salinity, and temperature altered the rocks, causing the precipitation and crystallization of phases that are not otherwise in equilibrium. Plain Language Summary: Vera Rubin ridge (VRR) is an erosion‐resistant feature on the northwestern slope of Mount Sharp in Gale crater, Mars, and it contains the Fe (III) oxide mineral hematite. Hematite is an especially important mineral to study on the Martian surface because it commonly forms in the presence of liquid water. Identifying the processes that formed hematite on VRR can help constrain the history of liquid water in Gale crater. The Mars Science Laboratory Curiosity rover performed an extensive campaign on VRR to determine the geologic history of the ridge. Mineralogical data collected by the CheMin instrument of four rock samples drilled on and below the ridge demonstrate changes in the mineralogy and provide clues about the aqueous history of VRR. Red hematite is common across the ridge, but detection of gray hematite in one sample indicates the presence of localized coarse‐grained hematite, which commonly forms under warm temperatures. Minerals that form in acidic, saline solutions were found in two samples, indicating localized alteration in acidic and relatively salty waters. We hypothesize that multiple episodes of groundwater with variable pH, salinity, and temperature altered the sediments after they lithified. Key Points: Data from the CheMin X‐ray diffractometer demonstrate a variety of secondary alteration products on Vera Rubin ridge Hematite particle size changes across and below the ridge, and this change may be a marker of diagenetic reaction The aqueous history of Vera Rubin ridge was complex, with several fluid episodes that varied in temperature, salinity, and pH